A phase I study of the WT2725 dosing emulsion in patients with advanced malignancies - Siqing Fu (Nature Portfolio, 2021)
Abstract WT2725 is a Wilms’ tumor gene 1 (WT1)-derived-oligopeptide vaccine designed to induce WT1-specific cytotoxic T-lymphocytes against WT1+ tumors in human leukocyte antigen (HLA)-A*0201+ and/or HLA-A*0206+ patients. Here, we report the results of a phase I study of WT2725. In this phase I, open-label, dose-escalation and expansion two-part study, the WT2725 dosing emulsion was administered as a monotherapy to patients with advanced malignancies known to overexpress WT1, including glioblastoma. In part 1, 44 patients were sequentially allocated to four doses: 0.3 mg (n = 5), 0.9 mg (n = 5), 3 mg (n = 6), and 9 mg (n = 28). In part 2, 18 patients were allocated to two doses: 18 mg (n = 9) and 27 mg (n = 9). No dose-limiting toxicities were observed, so the maximum tolerated dose was not reached. Median progression-free survival was 58 (95% confidence interval [CI] 56–81) days (~ 2 months) across all patients with solid tumors; median overall survival was 394 days (13.0 months) (95% CI 309–648). Overall immune-related response rate in solid tumor patients was 7.5% (95% CI 2.6–19.9); response was most prominent in the glioblastoma subgroup. Overall, 62.3% of patients were considered cytotoxic T-lymphocyte responders; the proportion increased with increasing WT2725 dosing emulsion dose. WT2725 dosing emulsion was well tolerated. Preliminary tumor response and biological marker data suggest that WT2725 dosing emulsion may exert antitumor activity in malignancies known to overexpress the WT1 protein, particularly glioblastoma, and provide a rationale for future clinical development. Trial registration: NCT01621542.